2020
DOI: 10.1080/00140139.2019.1710576
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of RAMP II - a practitioner’s tool for assessing musculoskeletal disorder risk factors in industrial manual handling

Abstract: RAMP II is an observation-based tool developed for assessing a wide range of musculoskeletal disorder risk factors related to industrial manual handling. RAMP II, which is part of the RAMP tool, is based on research studies and expert judgments. The assessment relies mainly on direct or video observations of the work being assessed, but additionally on measured push/pull forces and weights of handled objects, and on perceived workload and discomfort. Over 80 practitioners participated in the development of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 173 publications
(227 reference statements)
0
28
0
Order By: Relevance
“…While both can collect a large range of exposures, they often provide crude estimations of biomechanical exposures. They also often have low reliability and validity for ratings of movements and for upper-limb postures [ 26 , 27 , 28 , 29 , 30 ]. Therefore, technical instruments, such as accelerometer-based inclinometers, may be used to improve the accuracy and precision of these measurements [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…While both can collect a large range of exposures, they often provide crude estimations of biomechanical exposures. They also often have low reliability and validity for ratings of movements and for upper-limb postures [ 26 , 27 , 28 , 29 , 30 ]. Therefore, technical instruments, such as accelerometer-based inclinometers, may be used to improve the accuracy and precision of these measurements [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such risk assessments are often performed by professional ergonomists with the direct or indirect support of observation-based assessment tools [ 14 , 24 , 25 ]. Despite the broad applicability of observation-based assessment tools [ 26 , 27 ], they can have low precision and reliability [ 28 , 29 ], and can additionally be less cost-efficient than technical measurement instruments when considering the precision of the obtained data [ 30 ]. To compensate for such disadvantages, the assessment of risk factors for MSDs by using observation-based assessment tools may benefit from being complemented with increased use of technical measurement instruments [ 31 ], such as sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the duration of stationary levels would aid in this interpretation. Additionally, ergonomics literature has reported that for every 10 min of work a 90 s rest is required [31]; thus, it will be interesting to understanding whether MWC users achieve the recommended rest to work ratios and how this correlates to pathology development among MWC users.…”
Section: Discussionmentioning
confidence: 99%